1998
DOI: 10.1002/(sici)1098-2264(199809)23:1<36::aid-gcc6>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of theTAL1 gene by t(1;5)(p32;q31) in patient with T-cell acute lymphoblastic leukemia

Abstract: TAL1 gene deregulation is frequent in T‐cell acute lymphoblastic leukemia (T‐ALL) and can result from translocations involving 1p32 or, more frequently, from a cytogenetically undetectable interstitial deletion of chromosome 1. This study presents a case of T‐ALL with a t(1;5)(p32;q31) involving TAL1, in which the breakpoint occurs approximately 10 kbp 5′ to the gene and leads to transcriptional activation and synthesis of a TAL1 protein, and extends the spectrum of recognized TAL1 gene translocations associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…3,23,24 Its deregulation resulted from a cytogenetically undetectable interstitial deletion of chromosome 1. 25,26 Such discrete abnormalities might juxtapose Hox11L2 and potentially activate sequences, which may be numerous in band 5q32, in view of the large number of active genes in this genomic region. Ongoing molecular characterization of chromosomal breakpoints may pinpoint the mechanisms implicated in Hox11L2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…3,23,24 Its deregulation resulted from a cytogenetically undetectable interstitial deletion of chromosome 1. 25,26 Such discrete abnormalities might juxtapose Hox11L2 and potentially activate sequences, which may be numerous in band 5q32, in view of the large number of active genes in this genomic region. Ongoing molecular characterization of chromosomal breakpoints may pinpoint the mechanisms implicated in Hox11L2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Split-signal FISH for translocations in ALL M van der Burg et al been reported: t(1;7)(p32;p35) involving the TCRB locus, with a breakpoint 35 kb downstream of the TAL1 coding sequences; 7 t(1;3)(p32;p21) involving the TCTA gene; 5,127 and t(1;5)(p32;q31) in which the exact partner gene has not yet been identified. 8 Like in t (1;14), the breakpoints in t(1;3) and t(1;5) are located in the 5' untranslated region of the TAL1 gene. Although aberrations in the TAL1 gene are the most common defects in T-ALL, no clear correlation was found between TAL1 gene aberrations and clinical outcome in a large series of 182 children with newly diagnosed T-ALL.…”
Section: Figurementioning
confidence: 99%
“…Ectopic TAL1 gene expression can also be induced by translocations involving TAL1. [5][6][7][8][9] Recently, a new recurrent, but cryptic translocation t(5;14)(q35;q32) has been described in T-ALL. 10,11 In the majority of patients with this translocation, the breakpoint is located within or downstream of the RANBP17 gene at 5q35; the breakpoints at 14q32 are very heterogeneous.…”
mentioning
confidence: 99%
“…In cases of leukemia, translocations of chromosome 1 band p32 (1p32) or a cryptic interstitial deletion at 1p32 are specifically associated with T lymphoblastic leukemia/lymphoma (T-ALL/LBL) [2,3]. Translocations with various partners such as 14q11, 7q35 or 3p21 occur in approximately 3% of T acute lymphoblastic leukemia (T-ALL) cases, but the t(1;5)(p32;q31) translocation has been reported only in two cases [3][4][5][6][7]. We present here an additional case of t(1;5)(p32;q31).…”
mentioning
confidence: 99%